AVALIAÇÃO SENSORIAL DE BISCOITO DE AVEIA ENRIQUECIDO COM LINHAÇA - KREUTZ, CARLA L.; BALLUS, CRISTIANO A.; REGINATTO, SABRINA; FAGUNDES, GILBERTO A.; VICENZI, RAUL; KLAJN, VERA M. (Salão do Conhecimento, 2013)
Resumo